(untitled) (Research, Society and Development, 2021)
The beauty standards established by society have been a determining factor in the increase of patients looking for cosmetic dentistry in order to obtain a symmetrical smile. Within this context, the most wanted dental treatments to improve the smiles appearance are the ones used to change the teeth color, shape, and size. This paper aims to report a case of an esthetic solution in which the patient complained about multiple diastemas after making an orthodontic treatment. The treatment chosen was the dental reanatomization of the elements 13 to 23 by the direct technique in composite resin with the help of palatal silicon index. The obtained results showed that the technique based on accurate prior planning is capable of solving esthetic cases quickly, safely, and predictably. Therefore, it was also possible to conclude that the composite resins allow the esthetic rehabilitation of the smile in a direct way, with a good cost-benefit and excellent results. In addition, it was observed that dental reanatomization may be necessary for the purpose of post orthodontic treatment in cases that require changes in dental proportions.